(untitled)
Starting in 2006 the German economy currently experiences a cyclical revival which spreads to the labor market. Unemployment decreases markedly and regular employment rises. At present, virtually all professional forecasts expect this upswing to continue in the foreseeable future. Against this background a debate has taken center stage as to what extent unemployment figures consist of merely cyclical components or, in other words, which part of joblessness can be labeled as ". " unemployment, however, is a loaded word since there is no clear cut consensus about its meaning, let alone its measurement. Hence, the question arises whether the on-accelerating inflation rate of unemployment"(NAIRU) may serve as a tool to determine the development and current level of non-cyclical unemployment and to frame policy discussions., address = Kiel, author = Bernd Fitzenberger and Wolfgang Franz and Oliver Bode, copyright = http://www.econstor.eu/dspace/Nutzungsbedingungen, keywords = 330, language = eng, number = 1344, publisher = Kiel Institute for the World Economy (IfW), title = The Phillips Curve and NAIRU Revisited: New Estimates for Germany, type = Kiel Working Paper, url = https://hdl.handle.net/10419/17859, year = 2007